Ethiopia : Well-Being and Poverty in Ethiopia, The Role of Agriculture and Agency - World Bank (Washington, DC, 2012)
A decade and a half of relative peace and political stability, broad economic reforms, and far-reaching political decentralization have brought Ethiopia back from one of its lowest levels of income per capita to one of its highest levels over the past forty years. At the same time, Gross Domestic Product per capita today is still only slightly above the levels reached in the early 1970 underscoring the deep-rooted and complex nature of poverty in Ethiopia. The positive developments at the macro level beg the questions of how well the Ethiopian people themselves fared during this period and what can be done to improve their lives further. These are the two overarching questions this study attempts to address, with a larger emphasis on analyzing the relative importance of the different determinants of people's well-being and their policy implications in light of the upcoming revision of Ethiopia's Sustainable Development and Poverty Reduction Strategy (SDPRP). In particular, the study seeks to identify areas of intervention to improve people's well-being and to provide the behavioral foundations for developing sector specific policies. For a comprehensive treatment of the challenges and opportunities related to the different sectors, the study refers to the World Bank Country Status Reports on Health, Education and Rural Development.